Studi Keberlanjutan IPAL Komunal di Kota Surabaya: Studi Kasus di RT 2 RW 12 Kelurahan Bendul Merisi Kota Surabaya - nilandita, widya; Pribadi, Arqowi; Nengse, Sulistiya; Auvaria, Shinfi Wazna; Nurmaningsih, Dyah Ratri (Al-Ard: Jurnal Teknik Lingkungan, 2019)
The increase in population is directly proportional to the increase in the amount of clean water. Nearly 80% of clean air becomes waste water. Before being discharged into an air body, waste water needs to be processed first. Operation of WWTP The goal is to treat wastewater to be safely disposed of into the environment. One area that has a communal WWTP is RT 2 RW 12, Bendul Merisi Sub-District, Wonocolo District, Surabaya City. The purpose of this study was to examine the sustainability of communal WWTP in RT 2 RW 12 Bendul Merisi Village, Wonocolo District, Surabaya City. This research is quantitative and quantitative. Communal WWTP at RT2 RW 12, Bendul Merisi Village, Wonocolo District, Surabaya City. Technical aspects have good sustainability status (83.48%), access features are included in a fairly sustainable category (71.38%), institutional aspects have a fairly sustainable sustainability status (56.54%) and economic aspects have a less sustainable sustainability status ( 50%). The results of the study showed that the sustainability status of communal WWTP in RT2 RW 12, Bendul Merisi Subdistrict, Wonocolo Sub-District, Surabaya City was included in the fairly sustainable category (63.85%).